Advanced cathodes and electrolytes for rechargeable zinc-ion batteries - Verma, Vivek (Nanyang Technological University, 2021)
Increasing energy demands has led to the rise in the harvest of renewable energy sources such as solar and wind energy for grid-scale energy storage. However, the intermittent energy output from these resources demand efficient ways to store the electrical energy. Rechargeable batteries can be a promising technology. However, the widely used Li-ion batteries might not be apt for grid-scale storage application considering the rising cost of Li metal and safety concerns. Rechargeable Zinc-Ion batteries (RZIBs) can be a better alternative to Li-ion batteries. RZIBs use zinc metal as an anode which is 1) inexpensive, recyclable, and easier to handle, 2) has a higher volumetric capacity than Li metal and 3) Zn is divalent and hence can theoretically transfer twice the charge per ion when compared to Li. However, the present RZIBs show a severe capacity fading during cycling and a limited operational lifetime. A poor operational lifetime will mean frequent replacement of the battery pack which at a large grid-scale level will not be very economical. This suboptimal performance is due to a lack of better cathode materials and the electrolyte formulations. The aim of this thesis is two-fold: First, this thesis explores different classes of cathode materials as a reversible zinc-ion storage host. Phosphate based intercalation-type cathode materials were tested and in-depth zinc-ion intercalation mechanism was elucidated. Furthermore, as an alternative to the intercalation-storage mechanism, reversibly storing zinc-ions via conversion-type mechanism was demonstrated for the first time and the conversion mechanism was elucidated in depth. Second, the electrolyte formulations were found to initiate a lot of undesired reactions which also limits the battery operational lifetime. Hence novel electrolyte formulations were designed to limit the undesired reactions. Using the developed cathodes and electrolyte formulations, full cell RZIB battery performance with high operational lifetimes were demonstrated. The results and the various strategies adopted in designing the cathode materials and the electrolyte formulations should provide necessary guidelines in improving the RZIB performance on a practical scale.